2009
DOI: 10.1007/s00415-009-5255-7
|View full text |Cite
|
Sign up to set email alerts
|

Non-motor symptoms in atypical and secondary parkinsonism: the PRIAMO study

Abstract: The PRIAMO study is a cross-sectional longitudinal observational study aimed at describing epidemiology and evolution of non-motor symptoms (NMS) in patients with different forms of parkinsonism recruited in 55 Italian centres and evaluated over 24 months. In this paper, we are reporting prevalence and clinical characteristics of NMS in patients with atypical and secondary parkinsonism. Out of 1307 consecutive patients with a diagnosis of parkinsonism, 83 patients had vascular parkinsonism (VP), 34 had multipl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
154
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 139 publications
(164 citation statements)
references
References 34 publications
8
154
1
Order By: Relevance
“…Another data comparing sleep disturbances in patients with PD, MSA and PSP demonstrated that patients with MSA showed higher risk of OSA and less frequent RLS 26 . The PRIAMO study, which analyzed non-motor symptoms in atypical and secondary parkinsonism, found that sleep disturbances were also common with a prevalence of approximately 70% in all diagnostic groups, including MSA patients 27 . RBD and nocturnal stridor are considered red flags and may be the first symptoms of the disease 22 .…”
Section: Sleep Disorders In Sporadic Ataxiasmentioning
confidence: 99%
“…Another data comparing sleep disturbances in patients with PD, MSA and PSP demonstrated that patients with MSA showed higher risk of OSA and less frequent RLS 26 . The PRIAMO study, which analyzed non-motor symptoms in atypical and secondary parkinsonism, found that sleep disturbances were also common with a prevalence of approximately 70% in all diagnostic groups, including MSA patients 27 . RBD and nocturnal stridor are considered red flags and may be the first symptoms of the disease 22 .…”
Section: Sleep Disorders In Sporadic Ataxiasmentioning
confidence: 99%
“…1 Plausible mechanisms linking migraine with movement disorders include damage to relevant brain structures previously associated with migraine, 2 dopamine (DA) dysfunction (which has been hypothesized as a causal factor in migraine pathogenesis), 3 parkinsonism due to head injury or ischemic vascular disease (both of which are linked to migraine), [4][5][6] or damage related to iron deposition in the basal ganglia and related structures (also previously linked to migraine). [7][8][9][10] However, with the exception of restless legs syndrome (RLS), also known as Willis-Ekbom disease (WED), 11,12 the relationship between migraine and movement disorders has only been examined in samples specifically selected for presence of clinically diagnosed migraine or movement disorders, or in older cohorts when headache symptoms are retrospectively assessed.…”
mentioning
confidence: 99%
“…Eight studies were conducted in Europe [17,18,19,20,21,22,23,24,25] and two studies in the USA [26,27]. Five studies examined outcomes in nursing homes [23,24,25,26,27], whereas five studies examined outcomes in community-dwelling people or patients recruited from outpatient clinics [17,18,20,21,22].…”
Section: Resultsmentioning
confidence: 99%
“…Five studies examined outcomes in nursing homes [23,24,25,26,27], whereas five studies examined outcomes in community-dwelling people or patients recruited from outpatient clinics [17,18,20,21,22]. Five studies were cross-sectional [17,21,22,24,25,27], two longitudinal observational studies [19,23], one was a case-control study [18], one a retrospective cohort study [26] and one a randomized controlled trial [20]. The mean subject age ranged from 70 to 86 years.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation